Knowledge and practice regarding menstrual hygiene and alternatives to sanitary pad among Indian undergraduate medical students: A cross-sectional study - Y C Nalini; Sonal Gaonkar; I B Anjusha; Abhishekh Basavarajegowda (Wolters Kluwer Medknow Publications, 2022)
INTRODUCTION: While the availability and use of disposable sanitary pads have increased considerably in the last two decades, awareness about disposal and menstrual waste management has been neglected. This study was designed to determine the knowledge and practice of sanitary pad usage, disposal, and alternative methods of menstrual hygiene attitude toward menstrual leave among Indian undergraduate medical students. MATERIALS AND METHODS: The study participants were Indian undergraduate medical students. Self-administered online questionnaires were utilized, using Google Forms that requested personal details, menstrual history, usage and disposal of the sanitary pad, alternatives to the sanitary pad, and opinions about paid menstrual leave or sick leave policy. Quantitative data were summarized using mean and standard deviation, whereas qualitative data were summarized using percentages and frequencies. Data collected were analyzed using SPSS software version 20. RESULTS: Four hundred sixty-four students participated in the study. The mean age at menarche was 13 years. Menstrual bleeding lasted an average of 5.2 ± 1.6 days. Cycle length was 21-35 days in 92% of cases. Approximately 42.9% of respondents reported dysmenorrhea. 98% reported using the sanitary pad; among them, 48% reported they use a single pad (nonbio-degradable pads) for more than 6 h, and the most common mode of disposal is by wrapping in a newspaper. Menstrual cup followed by tampons is common alternatives to the sanitary pad. 48.7% reported that sometimes menstruation keeps them away from colleges. Eighty-two percent expressed menstrual leave policy of 1-2 days would be a positive and welcome move. CONCLUSIONS: Knowledge about sanitary pad disposal and alternatives is adequate among Indian undergraduate medical students but what is inadequate is the practice. Emphasis should be made on strategies that can be adopted to prevent the dumping of unsorted disposed of unsafe menstrual waste across the landfills resulting in a global health issue.